Integrative physiological and transcriptomic analysis provides insights on the molecular basis of ABA-enhanced drought tolerance in pear (Pyrus betulaefolia) - Guo-Ling Guo; An-Ran Luo; Yun-Hui Tan; Rui-Kang Yuan; Ting-Yue Luo; Pan-Pan Ma; Jun-Yu Zhan; Piao Han; Li Liu; Wei Heng; Zhenfeng Ye; Sheng Yang; et al. (BMC Plant Biology)
Abstract Background Drought stress could suppress the carbon assimilation and limit nutrient uptake of pear plants, thus affecting their growth and severely impacting the quality and yield of pear fruit. ABA is a stress hormone and is reported to alleviate drought stress in numerous plants. However, whether and how ABA functions in the drought responses of pear plants is yet explored. Results Here, to address this gap, pear seedlings (Pyrus betulaefolia) were used and subjected to PEG-induced drought conditions with or without additional ABA in various doses. The results showed that while drought caused severe leaf water loss and damage, applying ABA at 50 µM and 100 µM dramatically amended the phenomenon, as indicated by the markedly increased relative water content, and notably decreased relative electrolyte leakage and malondialdehyde content. Based on the results of RNA sequencing and related physiological indices, it was found that drought grossly disrupted chlorophyll synthesis and photosynthesis. It induced the over-production of reactive oxygen species (ROS) and broke the ROS homeostasis, despite the pronounced increases in ABA biosynthesis/content and signaling, flavonoid synthesis, and antioxidant enzyme activities, as well as sugar metabolism. However, ABA applications significantly elevated the expressions of genes in chlorophyll synthesis and photosynthesis, partially boosting the SPAD and Fv/Fm values. In addition, ABA treatments further prominently accelerate the synthesis processes of ABA, flavonoids, and antioxidant enzymes by up-regulating the corresponding genes, resulting in endogenous ABA accumulation and enzymatic activity improvement, thereby expediting the ROS scavenging. Of course, the sugar metabolism pathway was also outstandingly enhanced to balance the growth and stress response of pear seedlings. Moreover, through WGCNA analysis, the core turquoise module associated with ABA-attenuated drought stress was identified, and a portion of key transcription factors (TFs) and some hub genes were characterized, particularly for ERF, WRKY, MYB, bHLH, NAC in TFs, and CSP, COR, and DHN in hub genes. Overall, our study reveals that exogenous ABA could help pear plants to efficiently scavenge drought-induced ROS by improving their photosynthesis capacity, ABA accumulation, sugar catabolism, enzymatic antioxidant system, etc. These results will provide a scientific basis and practical direction for utilizing ABA to mitigate the adverse effects of water starvation resulting from the persistent high temperature on pear plants in summer. Conclusion 50 µM and 100 µM ABA application ameliorated the drought damage in pear seedlings, and the working routes are associated with reinforcement in the photosystem, ABA biosynthesis and signaling, flavonoid accumulation, and sugar metabolism, as well as enzymatic activities in ROS scavenging. The relevant regulatory network is complex, primarily concerned with ERF, WRKY, MYB, bHLH, and NAC TFs, with a focus on the potential target genes named CSP, COR, and DHN.